A Single Large Center Experience of Medically Treating Impending Compartment Syndrome of Tibia with Deflazacort - Chanchal Kumar Singh; Ghanshyam Narayan Khare; Prabhanjan Agrawal (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Acute compartment syndrome (ACS) is a rare condition characterized by increased pressure in the closed compartments of the limbs resulting in ischemic tissue necrosis. Most of the patients present following limb fractures. Apart from surgical options such as fasciotomy, which has inherent complication of myonecrosis and severe infection, conservative management with corticosteroids hasshown to be useful. We conducted this study to understand the changes in intra-compartment pressures in ACS after regular monitoring following corticosteroids treatment. Materials and Methods: Consecutive patients of ACS following closed fractures lower limb fractures of tibia or fibula from June 2021 to February 2022 were included. The intra-compartment pressure was measured using a manometer at the time of presentation and after 3, 6, 12, 24, 48, 72, and 96 h of treatment with tab Deflazacort 6 mg × 1 Tablet × Tds. The efficacy of treatment was assessed on the basis of changes in intra-compartmental pressure and improvement in the clinical signs and symptoms of ACS. Results: The study included 60 patients, most (63.3%) suffering from fracture of proximal tibia or fibula (36.7%), presenting with ACS. The mean age was 32.4 ± 8.6 years and most (53%) were males. We observed a statistically significant change (P < 0.05) in the intra-compartment pressures from the baseline to 3 h, 24 h, 48 h, 72 h, and 96 h after corticosteroid treatment. None of these patients suffered from ischemic necrosis or any other complication of ACS. Conclusion: Our results suggest that the timely diagnosis of ACS in patients with lower limb fractures and early initiation of conservative management with corticosteroids can be a mainstay of treatment in these patients. This conservative approach can avoid surgical intervention and reduce the cost of management.